A Critical Evaluation of Task Design in Bright: An English Textbook for Grade 8 Based on TBLT Principles - Natasya Putri Maharani; Acep Bahrum Kamil; Dedeh Kartini (PROJECT (Professional Journal of English Education), 2026)
This study aims to evaluate the extent to which the tasks in Bright: An English textbook for Grade 8 align with the principles of Task-Based Language Teaching (TBLT). This study employed a qualitative research design using content analysis. The data were taken from three selected chapters representing the beginning, middle, and end of the textbook. The tasks were analyzed using criteria adapted from TBLT principles, including meaning focus, communicative gap, learner language use, communicative outcome, and interaction. The findings reveal that the tasks are only partially aligned with TBLT principles. While some activities promote meaningful communication and interaction, the majority of tasks are dominated by form-focused exercises such as fill in the blank, matching, and sentence completion. These activities limit students’ opportunities to engage in real life communication. It can be concluded that the textbook does not fully support the implementation of TBLT. Therefore, teachers are encouraged to adapt the tasks to make them more communicative, and textbook developers should incorporate more task-based activities to better support communicative language learning.